2006
DOI: 10.1002/jcb.20951
|View full text |Cite
|
Sign up to set email alerts
|

Modified HMG‐CoA reductase and LDLr regulation is deeply involved in age‐related hypercholesterolemia

Abstract: During the ageing process in rats hypercholesterolemia occurs in concert with full activation, lowered degradation rate and an unchanged level of the rate limiting cholesterol biosynthesis enzyme, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoAR). The molecular bases of the HMG-CoAR unchanged level and lowered degradation rate in aged rats is not clear. In fact no data are available during ageing, on transcription and degradation of HMG-CoAR, so well defined in adult animal. So, aim of this work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…These processes are also directly or indirectly modulated by hormones such as estrogens, thyroid hormones and insulin [20,68,80,92]. During ageing, an increase of LDLr mRNA and protein has been reported, but a decrease of its membrane exposition has been observed.…”
Section: Cholesterol Cellular Traffickingmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes are also directly or indirectly modulated by hormones such as estrogens, thyroid hormones and insulin [20,68,80,92]. During ageing, an increase of LDLr mRNA and protein has been reported, but a decrease of its membrane exposition has been observed.…”
Section: Cholesterol Cellular Traffickingmentioning
confidence: 99%
“…During ageing, an increase of LDLr mRNA and protein has been reported, but a decrease of its membrane exposition has been observed. This contributes to the age-related hypercholesterolemia and cardiovascular disorders [10,92].…”
Section: Cholesterol Cellular Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular base of the unchanged HMGCR level and the lowered degradation rate in aged rats is not clear. Pallottini et al reported that the proteins involved in cholesterol homeostasis−HMGCR, Insig-induced gene (Insig) protein, sterol regulatory element binding protein (SREBP), SREBP cleavage activating protein (SCAP), and low density lipoprotein receptor (LDLr)−are modified in age-related hypercholesterolemia [18]. Even though we did not examine the molecular mechanisms underlying changing cholesterol metabolism with aging, our group is now investigating the effects of fenofibrate on the factors involved.…”
Section: Discussionmentioning
confidence: 94%
“…22 Hypercholesterolemia observed during aging can be explained by the change in homeostasis between the many signaling and metabolic constituents of the cholesterol signaling pathway that includes transcriptional regulation of 3-hydroxy-3-methylglutaryl coenzyme A reductase and LDL receptor (LDLR), which, in turn, are dependent on sterol regulatory element-binding proteins. 23 Caloric restriction, which generally refers to a chronic 20% to 40% reduction in calorie intake compared with ad libitum consumption, is well established to reduce cholesterol levels and alleviate its detrimental effects. 24 Martini et al investigated whether the beneficial effects of CR are because of its impact on the cholesterol biosynthesis and signaling pathway, specifically 3-hydroxy-3-methylglutaryl coenzyme A reductase and LDLR.…”
mentioning
confidence: 99%